Pengaruh Jus Tomat Terhadap Kadar Hemoglobin Pada Calon Pengantin Di Wilayah Kerja Puskesmas Sukorame Kecamatan Mojoroto Kota Kediri Tahun 2024: THE EFFECT OF TOMATO JUICE ON HEMOGLOBIN LEVELS IN PROSPECTIVE BRIDES - Awatiszahro , Alfika; Lutfiasari, Dessy; Nirwana, Betanuari Sabda; Saidah, Halimatus; Dewi , Rahma Kusuma; Sukmawati, Arum (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Background: The incidence of anemia in prospective brides in Indonesia is quite high. Based on the data, around 17.8% of prospective brides and grooms experience anemia. In addition, around 18% of prospective brides and grooms also experience chronic malnutrition. Overall, around 50.5% of prospective brides and grooms have health problems before marriage, including anemia. Objective: The purpose of this study was to identify the hemoglobin levels of prospective brides and grooms before and after being given Tomato Juice. Methods: This study is a pre-experimental study with a One Group Pretest-Postest design. The population in this study were all female prospective brides at the Sukorame Health Center, Mojoroto District, Kediri City in 2024. The sampling technique used was a purposive sampling technique with a sample size of 20 respondents, the statistical test used was the Paired T-Test because the data was normally distributed. Results: The hemoglobin levels of respondents before being given tomato juice had a minimum value of 11.22 gr / dl and the hemoglobin levels of respondents after being given tomato juice had a mean value of 11.97 gr / dl, a difference of 0.75 gr / dl was obtained. The statistical test results obtained a p value of 0.001 which is smaller than 0.05. So it can be concluded that H0 is rejected and H1 is accepted, which means that there is an effect of giving tomato juice on increasing the level of prospective brides. Conclusion: Tomato juice can be used as an alternative or addition to help overcome anemia in prospective brides.